(3MGTjI Ydi TQM GdETGQGJs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3Cf jbOe GdfbV Ydi GdefGbVI hgeG Ydi GdeYGQVI, hEPG KHJ gPG GdJUhjQ afbhd Pdc GdGYJQGV fbV GLeGdj hJbQjQg Cf GdOdjd Ydi GKHGJ GdUhQI aj Gdadc djS HJGes
(3BNQgG (B:s
(3BNQgG(B: (3CLGH HCf GdfGFe de jJNjd dG SjeG ajeG Gdfhe hGdjbXI Ch aj GdTF GdVQhQj cGdfaS Ch aj eG jUjQ VQhQjG ceG EPG QCi aj efGeg TjFG bO jRYL(B. (3gPG BNQ GdcdGe Ydi GdWHjYjGJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs